Point-of Care for Prompt Management of Infectious Meningitis and/or Encephalitis (IM/IE) in Gabon Military Hospital - Mangouka, Laurette Guignali; Iroungou, Berthe Amélie; Moussavou-Boundzanga, Pamela; TSBM, Aurore Bouassa; Nzenze, Jean Raymond (Archives of Clinical and Biomedical Research, 2022)
Infectious meningitis (IM) and/or infectious encephalitis (IE) can cause significant and irreversible damage to the central nervous system. Objective The main objective of the study was to identify a pathogen which causes IM or Meningoencephalitis (M/E) and evaluate the contribution of FilmArray (FA) M/E in patient management. Material and Method Twenty-one (21) cerebrospinal fluid (CSF) samples tested simultaneously using the FilmArray M/E and bacteria culture. Each sample was tested per the manufacturer’s instructions. Results We received CSF from 21 patients, including one infant and children from three departments: pediatric, internal medicine and intensive care. Among all patients, 12 are living with HIV, 2 had trypanosomiasis and 7 were immunocompetent. Median age 41 years with an age range from 1 to 75 years. The sex ratio was 3,5. Only 3 patients presented with pneumococcal meningitis and including one living with HIV. The cultures incubation time took from 3 to 5 days and the Point-of-care testing took an hour and a half to perform. Conclusion The detection of Mycobacterium tuberculosis in CSF samples is not yet included in all detection systems like GeneXpert or BioFire. We believe that in many epidemic areas for these diseases, developing tools to diagnose Mycobacterium tuberculosis or Toxoplasma gondii meningitis would be an important asset to help in the management of meningitis. Viruses remain a real problem for clinical diagnosis in countries with limited resources, therefore point-of-care development could improve treatment and reduce mortality.